The IMPLEMENTATION OF SYSTEM DOOR ACCES USING FACE RECOGNITION AND FINGER PRINT FOR MUNITIONS WAREHOUSE WITH A BASE HAAR CASSCADE - Mahfudi, Isa; Asari, M. Sofyan; Minggu, Desyderius (Pustaka Poltekad, 2021)
Abstract: Technology in the military world has been growing with the existence of technological innovations that are used to secure munitions warehouses. This is done to reduce the negligence of the munitions warehouse guard personnel if they lose the key from the munitions warehouse it can be monitored in real-time to find out who is around the munitions warehouse door. Thus, face recognition and fingerprint technology were created as a system for securing munitions warehouses, as well as the function is to be a CCTV. So, they can be monitored in real-time. This research method uses an experimental method to obtain quantitative data to prove the hypothesis data that use the Haar Cascade. The results of this study indicate that this security system has a very important role to limit access to and from the munitions warehouse and reduce the occurrence of theft or misuse of munitions. In the tests carried out, the minimum detection distance was 20 cm and the maximum distance that was able to detect was 110 cm. this is influenced by the focus of the camera and testing of the intensity of light in the morning, afternoon, evening, and night can be detected except detection at night without light and must use a fingerprint.